Isolation of Halotolerant Thermus spp. from Submarine Hot Springs in Iceland - Kristjansson, Jakob K. (1986)
Thermophilic, aerobic bacteria of the genus Thermus were isolated from submarine alkaline hot springs in Iceland. Five submarine hot springs were sampled, and all had viable counts of Thermus spp. of about 10(3) CFU/ml. All submarine strains grew in the presence of NaCl at 3% or higher, but no strains from terrestrial hot springs would grow at concentrations higher than 1% NaCl. The growth rate of submarine Thermus strains was not stimulated by NaCl and was reduced at NaCl concentrations higher than 1%. The pattern of growth of these isolates on single carbon sources was similar to that of terrestrial isolates.